Entrepreneurial leadership and competitive strategy in family business - Saiz Alvarez, Jose Manuel; Palma-Ruiz, Jesus Manuel 1978- (IGI Global, 2019)
"This book examines business strategies applied to family business that will boost efficiency, competitiveness, and optimal use of resources' allocation in companies competing internationally"--